28-year late spermatic cord relapse of a testicular non-seminomatous germ cell tumour, managed robotically - Hayes, James R.; Jewett, Michael A.S.; Hamilton, Robert J. (Canadian Urological Association Journal, 2016)
We present a patient who relapsed symptomatically 28 years postorchiectomy, initially followed by active surveillance for clinical stage I non-seminomatous germ cell tumour (CSI NSGCT). His relapse was localized to the pelvis, managed with robotic surgery, and achieved a complete resection with tumour markers normalized. We highlight the current Princess Margaret guidelines for followup of CSI NSGCT and discuss the trade-off between lifelong radiographic surveillance to detect the very small risk of late relapse. We discuss the incidence and presentation of late relapse, treatment options, and outcomes, highlighting that these tumours are typically refractory to chemotherapy and can often be managed with surgery alone.